A New Spectrophotometric Method for Determination of Selenium in Cosmetic and Pharmaceutical Preparations after Preconcentration with Cloud Point Extraction - Mohammad Hosein Soruraddin; Rouhollah Heydari; Morteza Puladvand; Mir Mehdi Zahedi (International Journal of Analytical Chemistry)
A simple, rapid, and sensitive spectrophotometric method for the determination of trace amounts of selenium (IV) was described. In this method, all selenium spices reduced to selenium (IV) using 6 M HCl. Cloud point extraction was applied as a preconcentration method for spectrophotometric determination of selenium (IV) in aqueous solution. The proposed method is based on the complexation of Selenium (IV) with dithizone at pH < 1 in micellar medium (Triton X-100). After complexation with dithizone, the analyte was quantitatively extracted to the surfactant-rich phase by centrifugation and diluted to 5 mL with methanol. Since the absorption maxima of the complex (424 nm) and dithizone (434 nm) overlap, hence, the corrected absorbance, Acorr, was used to overcome the problem. With regard to the preconcentration, the tested parameters were the pH of the extraction, the concentration of the surfactant, the concentration of dithizone, and equilibration temperature and time. The detection limit is 4.4 ng mL-1; the relative standard deviation for six replicate measurements is 2.18% for 50 ng mL-1 of selenium. The procedure was applied successfully to the determination of selenium in two kinds of pharmaceutical samples.